Spatio‐temporal assessment of illicit drug use at large scale: evidence from 7 years of international wastewater monitoring. (23rd October 2019) - González‐Mariño, Iria; Baz‐Lomba, Jose Antonio; Alygizakis, Nikiforos A.; Andrés‐Costa, Maria Jesús; Bade, Richard; Bannwarth, Anne; Barron, Leon P.; Been, Frederic; Benaglia, Lisa; Berset, Jean‐Daniel; Bijlsma, Lubertus; Bodík, Igor; et al.
Abstract: Background and aims: Wastewater‐based epidemiology is an additional indicator of drug use that is gaining reliability to complement the current established panel of indicators. The aims of this study were to: (i) assess spatial and temporal trends of population‐normalized mass loads of benzoylecgonine, amphetamine, methamphetamine and 3, 4‐methylenedioxymethamphetamine (MDMA) in raw wastewater over 7 years (2011–17); (ii) address overall drug use by estimating the average number of combined doses consumed per day in each city; and (iii) compare these with existing prevalence and seizure data. Design: Analysis of daily raw wastewater composite samples collected over 1 week per year from 2011 to 2017. Setting and Participants: Catchment areas of 143 wastewater treatment plants in 120 cities in 37 countries. Measurements: Parent substances (amphetamine, methamphetamine and MDMA) and the metabolites of cocaine (benzoylecgonine) and of Δ 9 ‐tetrahydrocannabinol (11‐nor‐9‐carboxy‐Δ 9 ‐tetrahydrocannabinol) were measured in wastewater using liquid chromatography–tandem mass spectrometry. Daily mass loads (mg/day) were normalized to catchment population (mg/1000 people/day) and converted to the number of combined doses consumed per day. Spatial differences were assessed world‐wide, and temporal trends were discerned at European level by comparing 2011–13 drug loads versus 2014–17 loads. Findings: Benzoylecgonine was the stimulant metabolite detected at higher loads in southern and western Europe, and amphetamine, MDMA and methamphetamine in East and North–Central Europe. In other continents, methamphetamine showed the highest levels in the United States and Australia and benzoylecgonine in South America. During the reporting period, benzoylecgonine loads increased in general across Europe, amphetamine and methamphetamine levels fluctuated and MDMA underwent an intermittent upsurge. Conclusions: The analysis of wastewater to quantify drug loads provides near real‐time drug use estimates that globally correspond to prevalence and seizure data.